Ressources pastorales et territorialité chez les agro-éleveurs sahéliens du Gourma des buttes - Fabrice Gangneron (VertigO)
The rural Hombori’s population (Mali) practice almost millet cultivation associated with small non transhumant breeding. Beyond the environmental constraints of a semi-arid region, the agro-livestock stability depends on two different parameters, the territorial control and the resource control. For example, sedentary agro-pastoralists desire “possessive rights” on land around them village while herders, seasonal visitors with whom they compete want pasture areas for them wherever they are. Moreover, water resources aren’t considered by users as “territorialials resources” and they are only appropriated when they are built. The cases of this study show that for low control, these production systems, structurally weak, can fail during low rainfall years.